Asthma and atopic disease in immigrants from Asia and the West Indies. Issue 674 (December 1981) - Morrison-Smith, John; Cooper, Susan M.
Abstract : The clinical pattern of asthma and atopic disease was compared in 2331 children of European, Asian and West Indian parentage seen in Birmingham in the past 10 years. The main findings were that a higher proportion of children born in England of all races developed asthma within the first 4 years of life than children born abroad; the sex ratio of roughly 2 boys to every girl with asthma was similar in each race wherever born; the ratio of persistent to intermittent asthma was similar in each race wherever born; there was no difference in the proportion with eczema between the racial groups; hay fever and pollen allergy was less frequent in Asian and West Indian children even if born in England; hospital admission was more frequent in immigrant groups; positive skin reactions to grass pollen and domestic animals were more frequent in European children than in immigrants but positive reactions to house-dust mites were less frequent in European children. It was considered that most differences could be explained on the basis of differences in environmental conditions and were unlikely to be of genetic origin.